2022
DOI: 10.3389/fpubh.2022.913255
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Recognition and Analysis of Negative Emotions of Undergraduates Under COVID-19

Abstract: BackgroundThe outbreak and spread of COVID-19 has brought a tremendous impact on undergraduates' study and life, and also caused anxiety, depression, fear and loneliness among undergraduates. If these individual negative emotions are not timely guided and treated, it is easy to cause the amplification of social negative emotions, resulting in individual and collective irrational behavior, and ultimately destroy social stability and trust foundation. Therefore, how to strengthen the analysis and guidance of neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…The ten negative emotions were anxiety, sadness, stress, frustration, despair, loneliness, fatigue, anger, depression, and fear. All of these negative emotions found are consistent with findings from other research studies, such as in (Ahmet & Ayşe, 2020;Onyeaka, 2021;Zhang, 2022).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The ten negative emotions were anxiety, sadness, stress, frustration, despair, loneliness, fatigue, anger, depression, and fear. All of these negative emotions found are consistent with findings from other research studies, such as in (Ahmet & Ayşe, 2020;Onyeaka, 2021;Zhang, 2022).…”
Section: Resultssupporting
confidence: 92%
“…Anxiety was identified as the primary emotion experienced during the pandemic, this is also consistent with other research, such as in (Tzaflkou, et al, 2021;Onyeaka, 2021;Zhang, 2022;Saeed, 2022). Sadness, stress and fear are the other negative emotions mostly reported as part of the global pandemic process.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Negative emotions are defined as the subjective feelings and emotional states of individuals who are depressed and continue to fall into unhappiness-activated states, such as depression, tension, anxiety, and stress (Lovibond and Lovibond, 1995 ). Many studies have shown that negative emotions tend to affect medical workers and college students during the COVID-19 pandemic (Han et al, 2022 ; Shreffler et al, 2020 ; Yin et al, 2021 ; Zhang, 2022 ). Nursing students exhibit negative emotions (Zou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%